An approach for exploring interaction between two proteins in vivo - Qadota, Hiroshi; Benian, Guy M. (Frontiers in Physiology, 2014)
We describe a strategy for exploring the function of protein-protein interactions in striated muscle in vivo. We describe our experience using this strategy to study the interaction of UNC-112 (kindlin) with PAT-4 (integrin linked kinase). Random mutagenesis is used to generate a collection of mutants that are screened for lack of binding or gain of binding using a yeast 2-hybrid assay. The mutant proteins are then expressed in transgenic C. elegans to determine their ability to localize in the sarcomere. We emphasize two advantages of this strategy: (1) for studying the interaction of protein A with protein B, when protein A can interact with multiple proteins, and (2) it explores the function of an interaction rather than the absence of, or reduced level of, a protein as can be obtained with null mutants or knockdown by RNAi. We propose that this method can be generalized for studying the meaning of a protein-protein interaction in muscle for any system in which transgenic animals can be generated and their muscles can be imaged.